2017
DOI: 10.1007/s10741-016-9593-0
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle inflammation and atrophy in heart failure

Abstract: Heart failure represents a systemic disease with profound effects on multiple peripheral tissues including skeletal muscle. Within the context of heart failure, perturbations in skeletal muscle physiology, structure, and function strongly contribute to exercise intolerance and the morbidity of this devastating disease. There is growing evidence that chronic heart failure imparts specific pathological changes within skeletal muscle beds resulting in muscle dysfunction and tissue atrophy. Mechanistically, system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 114 publications
(151 reference statements)
3
34
0
2
Order By: Relevance
“…Heart failure can increase inflammation, cause lower protein synthesis than degradation, reduce mitochondrial function, increase reactive oxygen species (ROS), change hormone content such as angiotensin II (AngII) and insulin like growth factor 1 (IGF-1), thus leading to muscle atrophy (31). Here, we present that exercise can reverse the adverse pathways caused by heart failure, so as to alleviate muscle atrophy (Figure 2).…”
Section: Classical Pathways Of Exercise Protection For Muscular Atropmentioning
confidence: 79%
See 1 more Smart Citation
“…Heart failure can increase inflammation, cause lower protein synthesis than degradation, reduce mitochondrial function, increase reactive oxygen species (ROS), change hormone content such as angiotensin II (AngII) and insulin like growth factor 1 (IGF-1), thus leading to muscle atrophy (31). Here, we present that exercise can reverse the adverse pathways caused by heart failure, so as to alleviate muscle atrophy (Figure 2).…”
Section: Classical Pathways Of Exercise Protection For Muscular Atropmentioning
confidence: 79%
“…Chronic inflammation is one of the characteristics of muscle atrophy induced by heart failure (31). Exercise decreases the secretion of inflammatory factors such as TNF-α, IL-6, and Creactive protein (CRP), which can directly reduce the process of protein hydrolysis and catabolism, reduce the degree of muscle loss, so as to achieve the anti-inflammatory effect of exercise (32,33).…”
Section: Classical Pathways Of Exercise Protection For Muscular Atropmentioning
confidence: 99%
“…However, the molecular pathophysiology of skeletal muscle myopathy is not well understood. This pathology is characterized by multiple alterations, like mitochondrial dysfunction, systemic inflammation, oxidative stress, and decreased muscle strength (isometric force), and atrophy of oxidative fibres [31]. It was shown that heart failure also induces skeletal muscle myopathy, and free heme was detected in patients with chronic heart failure [32], thus implicating a potential cause for the mechanical impairment of the myocardium [19].…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, известно, что дифференциально экспрессируемый ген CYR61, относящийся к группе белков, связывающих инсулиноподобный фактор роста (IGF) (табл. 2), участвует в регуляции ангиогенного фактора VEGF через механизмы цитоскелетной механотрансдукции [20], а увеличение его экспрессии в скелетных мышцах как на уровне мРНК, так и на уровне белка было обнаружено у здоровых людей после физической нагрузки. Кроме того, было показано, что сывороточный уровень CYR61 коррелирует со смертностью в течение 6 мес.…”
Section: результатыunclassified